Bi-Semiderivations on Triangular Algebra (Contemporary Mathematics, 2025)
The intension of present study is to investigate the structure of bi-semiderivations on triangular algebra with the help of associated module homomorphism. Moreover, we prove that all bi-semiderivations φ on triangular algebra will act as inner bi-derivations under some specific conditions stated that φ(e, e) = 0 = φ(γ, γ), where e represents unity and γ stands for the module homomorphism.
Keywords: bi-semiderivation; module; triangular algebra